OPTIMIZATION OF CASH WAQF LINKED SUKUK (CWLS) DISTRIBUTION TO SUPPORT SUSTAINABLE INVESTMENT IN INDONESIA - Mubarok, Abiyyu Achmad Syahru; Luthfiansyah, Muhammad Helmy; Nugroho, Reynold Andika; Afif, Ahmad (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
The Indonesian Waqf Board (BWI) explains that there is a gap between the potential for cash waqf and its realization. To optimize this potential, the government supports the Cash Waqf Linked Sukuk (CWLS) instrument as an alternative financing for state development. This research aims to provide suggestions for channeling CWLS funds so that they are directed toward sustainable investment. The research approach used is a qualitative approach which focuses on analyzing the content of literature (literature research). The data used is secondary data originating from various reading sources in journals, books, and other libraries. The results of this research confirm that sustainable investment is in line with the urgency of Sharia economics, including achieving SDGs targets in Indonesia. The distribution of CWLS funds can be optimized by channeling funds to the procurement of equipment and technology to reduce air pollution. Apart from being able to fulfill social and environmental aspects, the distribution of these projects becomes an investment forum that is beneficial for the world and the hereafter and is sustainable.